2001
DOI: 10.1046/j.1468-1331.2001.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and cognitive impairment three months after stroke

Abstract: To investigate the cognitive capacities of a cohort of ischaemic or haemorrhagic stroke survivors and to identify the clinical determinants of post-stroke cognitive impairment, we evaluated 237 patients admitted to a Stroke Unit (mean age 59; SD=12.7). Three months after stroke, patients were submitted to a neuropsychological evaluation that included the Mini-Mental State Examination (MMSE), a complementary battery to assess specific cognitive domains, the Hamilton Depression Rating Scale (HDRS) and the Blesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
2
19

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 44 publications
7
115
2
19
Order By: Relevance
“…Um grande estudo realizado com extensa bateria neuropsicológica encontrou 55% dos pacientes com comprometimento em pelo menos um domínio cognitivo, 27% com outros déficits cognitivos sem prejuízo da memória, 7% com déficits somente em memória e 9% com prejuízos em memória e outros déficits cognitivos 46 47 .…”
Section: Aspectos Neuropsicológicosunclassified
“…Um grande estudo realizado com extensa bateria neuropsicológica encontrou 55% dos pacientes com comprometimento em pelo menos um domínio cognitivo, 27% com outros déficits cognitivos sem prejuízo da memória, 7% com déficits somente em memória e 9% com prejuízos em memória e outros déficits cognitivos 46 47 .…”
Section: Aspectos Neuropsicológicosunclassified
“…Epidemiological studies have indicated that the prevalence of dementia in ischemic stroke patients is nine-fold higher than in controls 3 months after the stroke (Pohjasvaara et al 1998;Madureira et al 2001) and 4-12 times higher than in controls 4 years after a lacuna infarct (Loeb et al 1992). Even so, the prevalence of VaD may have been under-estimated, as the incidence of dementia varies considerably depending on which criteria are applied (Pohjasvaara et al 2000).…”
Section: Ischemic Stroke and Vascular Dementiamentioning
confidence: 99%
“…Über die Konstruktion einer einfachen ätiopa-thogenetischen Reihe AH -Schlaganfall -vaskuläre Demenz (VD) ist die AH mit dem Syndrom Demenz verknüpft. Die Demenzinzidenz nach Schlaganfall wird in der Literatur mit 6-33% angegeben [52,59]. Für den Oberbegriff VD ist eine Reihe spezifischerer Unterteilungen vorgenommen worden.…”
unclassified